Medical Devices Transition to Information Systems: Lessons Learned - Charters, Kathleen G. (American Medical Informatics Association, 2012)
Medical devices designed to network can share data with a Clinical Information System (CIS), making that data available within clinician workflow. Some lessons learned by transitioning anesthesia reporting and monitoring devices (ARMDs) on a local area network (LAN) to integration of anesthesia documentation within a CIS include the following categories: access, contracting, deployment, implementation, planning, security, support, training and workflow integration. Areas identified for improvement include: Vendor requirements for access reconciled with the organizations’ security policies and procedures. Include clauses supporting transition from stand-alone devices to information integrated into clinical workflow in the medical device procurement contract. Resolve deployment and implementation barriers that make the process less efficient and more costly. Include effective field communication and creative alternatives in planning. Build training on the baseline knowledge of trainees. Include effective help desk processes and metrics. Have a process for determining where problems originate when systems share information.